2014
DOI: 10.3987/com-13-s(s)24
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Properties, and Crystal Structure of DDQ-Adducts of Ethynylated 2H-Cyclohepta[b]furan-2-ones

Abstract: -Ethynylated 2H-cyclohepta [b]furan-2-ones reacted with 2,3-dichrolo-5,6-dicyano-1,4-benzoquinone (DDQ) in a formal [2+2] cycloaddition reaction to afford the corresponding DDQ-adducts in good yields.The electronic properties of the DDQ-adducts were investigated by UV/Vis spectroscopy. One of the DDQ-adducts was revealed the molecular structure by X-ray crystallographic analysis. The redox behavior of the new compounds was examined by cyclic voltammetry (CV) and differential pulse voltammetry (DPV).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…Thus, we investigated the preparation of new TCBDs based on CHFs for the construction of multistage redox activec hromophores. The alkynes also reactedw ith TCNQ [58] and DDQ [59] to afford the corresponding addition products. Similar to TCBD derivatives with azulenyl substituents, CHF-substituted TCBDs 47-53 were obtained by the [2+ +2] CA-RE of the correspondinga lkynes with TCNE ( Figure 9).…”
Section: Heteroazulenylt Cbds With Aryl Substituentsmentioning
confidence: 96%
See 1 more Smart Citation
“…Thus, we investigated the preparation of new TCBDs based on CHFs for the construction of multistage redox activec hromophores. The alkynes also reactedw ith TCNQ [58] and DDQ [59] to afford the corresponding addition products. Similar to TCBD derivatives with azulenyl substituents, CHF-substituted TCBDs 47-53 were obtained by the [2+ +2] CA-RE of the correspondinga lkynes with TCNE ( Figure 9).…”
Section: Heteroazulenylt Cbds With Aryl Substituentsmentioning
confidence: 96%
“…Similar to TCBD derivatives with azulenyl substituents, CHF-substituted TCBDs 47-53 were obtained by the [2+ +2] CA-RE of the correspondinga lkynes with TCNE ( Figure 9). The alkynes also reactedw ith TCNQ [58] and DDQ [59] to afford the corresponding addition products. The CHF substituent on the alkyne acts as an activating group to promote the [2+ +2] CA-RE reaction, similar to 1-azulenyl groups.…”
Section: - 2- and 6-azulenyl Tcbds With Ferrocene Substituentsmentioning
confidence: 99%
“…[c] Reaction with 4,4'-(ethyne-1,2-diyl)bis(N,N-dimethylaniline) (11). [43] 2,3,5,6-Tetrahalo-1,4-quinones afforded different types of final products.T etrafluoroquinone 20 reacted with two equivalents of 15 upon heating in 1,2-dichloroethane to afford (AE)-21 in 20 %yield. substituted spiro derivative (AE)-19 in 16 %upon heating.…”
Section: Reactivity Of Halo-p-benzoquinonesmentioning
confidence: 99%
“…[42] Theh omoconjugated push-pull chromophores obtained by the [2+ +2] CA reaction as well as the subsequently formed spiro compounds showed ICT bands in the visible range and high third-order nonlinear optical (NLO) properties.T he same reactions were reported for the alkynes substituted by p-N,N-dihexylaniline,f errocene,a nd 2Hcyclohepta [b]furan-2-one donors. [43] 2,3,5,6-Tetrahalo-1,4-quinones afforded different types of final products.T etrafluoroquinone 20 reacted with two equivalents of 15 upon heating in 1,2-dichloroethane to afford (AE)-21 in 20 %yield. [44] Thefirst reaction in ac ascade of reactions is the [2+ +2] CA,s imilar to that of DDQ.I nc ontrast, chloranil (22)…”
Section: Reactivity Of Halo-p-benzoquinonesmentioning
confidence: 99%
“…In particular, a [2 + 2] CA adduct was prepared through the [2 + 2] CA-RE reaction. Studies have shown that the thermal treatment of the [2 + 2] CA adduct leads to the formation of a spiro compound [89][90][91][92][93][94]. Ester-substituted, electron-deficient alkenes have also been employed in [2 + 2] CA-RE reactions involving electron-rich alkynes.…”
Section: Review Click-type [2 + 2] Ca-re Reactionsmentioning
confidence: 99%